2013
DOI: 10.1007/s12651-013-0132-3
|View full text |Cite
|
Sign up to set email alerts
|

Arbeit zur falschen Zeit am falschen Platz? Eine Matching-Analyse zu gesundheitlichen Beanspruchungen bei Schicht- und Nachtarbeit

Abstract: Working at the wrong time at the wrong place? A matching-analysis on health stresses for shift and night work Abstract Many studies report diseases caused by shift and night work. As a rule, however, such studies do not take into account socio-demographic factors and job characteristics. Based on the BIBB/BAuA Employment Survey 2006, the present paper looks into the effects of various job-specific and socio-structural factors on physical and mental health as well as sleeping disorders. The analysis was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
1
2
0
2
Order By: Relevance
“…Permanent night workers more often work in services and less often in the public sector or industry compared to rotating night shift workers and employees in general. Further, we find that, compared to all dependent employees, night workers more often engage in work characterized by adverse physical and ambient working conditions as known from other representative German surveys, such as the BIBB/BAuA Employment Survey and the German Microcensus (Beermann 2010;Struck et al 2012; Bundesanstalt für Arbeitsschutz und Arbeitsmedizin 2015). Nevertheless, some differences between permanent night workers and rotating night shift workers also become apparent.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Permanent night workers more often work in services and less often in the public sector or industry compared to rotating night shift workers and employees in general. Further, we find that, compared to all dependent employees, night workers more often engage in work characterized by adverse physical and ambient working conditions as known from other representative German surveys, such as the BIBB/BAuA Employment Survey and the German Microcensus (Beermann 2010;Struck et al 2012; Bundesanstalt für Arbeitsschutz und Arbeitsmedizin 2015). Nevertheless, some differences between permanent night workers and rotating night shift workers also become apparent.…”
Section: Discussionsupporting
confidence: 58%
“…Other studies on night work found a similar pattern of results: Representative surveys showed that night workers were more often affected by adverse psychosocial demands, e.g. lack of decision latitude, monotone tasks, but especially physical demands, such as difficult body posture and heavy lifting, work with hazardous contaminants, noise and vibrancy exposure, and exposure chemicals, dust, smoke, or gas (Struck et al 2012;Liersch 2014).…”
Section: Working Conditionsmentioning
confidence: 62%
“…More recent studies have addressed the fact that classic cardiovascular risk factors (e.g., lack of exercise, smoking, diet) have a much greater impact on the health of employees than shift and night work (20). According to Struck et al (106), the health hazards of shift and night work are based more on "third-party variables" (e.g., socio-demographic influencing factors, stressful workplaces) that occur regardless of the working hours. The association between shift and night work and impaired health must be interpreted more cautiously and in a more differentiated manner.…”
Section: Discussionmentioning
confidence: 99%
“…Deshalb ist Schichtarbeit durch ein höheres Belastungspotenzial geprägt. Einige Studien weisen darauf hin, dass Schichtarbeit häufiger mit physischen [1,3,7], psychischen [8,9] und psychosozialen Belastungen [1,3] einhergeht. Auch verfügen Schichtarbeitende über weniger Ressourcen, wie etwa Kontroll-und Planungsmöglichkeiten, Einfluss auf Arbeitsmenge und -inhalt [3] sowie Anerkennung durch Vorgesetzte [1].…”
Section: Einleitung ▼unclassified